A comparative study of healthcare Quality Management Systems: Examining the effects on patient communication, service accessibility, and decision-making autonomy in Poland and Lebanon - Ahmad Dit Al Hakim, Samir (Polish Journal of Public Health, 2026)
Introduction. Quality Management systems enable healthcare organizations to deliver services ensuring patient safety, operational effi ciency, and process standardization. This study examines healthcare quality management in Poland and Lebanon, comparing patient interactions, service availability, and decision-making autonomy between centralized public and decentralized private healthcare models.Methods. A mixed-method cross-sectional study was conducted at Mount Lebanon Hospital (Lebanon) and the University Hospital of Lord’s Transfi guration (Szpital Kliniczny Przemienienia Pańskiego w Poznaniu) from October 2023 to March 2024. Structured surveys were administered to 88 respondents (44 patients, 44 doctors) regarding their perception of healthcare quality. Quantitative data was analyzed using descriptive statistics in R, while qualitative data underwent thematic analysis using ATLAS.ti.Results. Notable differences emerged in service accessibility, communication effectiveness, and autonomy in treatment decision. Lebanese participants rated service accessibility higher with fewer barriers to healthcare access. Communication scores were comparable; Lebanon emphasised provider-patient interpersonal dynamics while Poland focused on staff information transparency. Poland demonstrated signifi cantly higher decision autonomy, refl ecting greater patient engagement in healthcare decisions.Conclusions. Both healthcare systems show distinct strengths and improvement opportunities. Lebanon’s private system ensures effi ciency and patient interaction, while Poland’s public system promotes patient autonomy and care uniformity. Systems can enhance service delivery by adopting each other’s best practices.